Child homicide in northern Tunisia: a retrospective study of forensic autopsy cases - Meriem Grayaa (SpringerOpen, 2021)
Abstract Background As far as we know, no previous research has investigated child homicide in Tunisia. In this context, our study was carried out to analyze the epidemiological and medico-legal characteristics of child homicide occurring in northern Tunisia over a 17-year period. Results Eighty-seven cases were collected, with a male-to-female ratio of 2.4. The mean age of the victims was 12.6 years for both sexes. We found that 56.3% of the cases were aged between 15 and 18 years. The majority of deaths under 15 years of age occurred at home as a result of intrafamilial homicide. Victims aged more than 15 years were more likely to be assaulted outside the home by a non-family member. The most frequent method of homicide was sharp force (39%) affecting mostly the heart and the lung, followed by blunt trauma (25%), which affected mainly the head. Sexual assault was diagnosed at autopsy in six victims (6.9%). Conclusions The study offers available data concerning the patterns of child homicide in northern Tunisia and may help to implement preventive measures against this kind of crime.